2015
DOI: 10.1063/1.4928696
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular structure and dynamics of mequinol and guaiacol in the gas phase: Rotationally resolved electronic spectra of their S1 states

Abstract: The molecular structures of guaiacol (2-methoxyphenol) and mequinol (4-methoxyphenol) have been studied using high resolution electronic spectroscopy in a molecular beam and contrasted with ab initio computations. Mequinol exhibits two low frequency bands that have been assigned to electronic origins of two possible conformers of the molecule, trans and cis. Guaiacol also shows low frequency bands, but in this case, the bands have been assigned to the electronic origin and vibrational modes of a single conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Compared to the UV measurements, the accuracies of the GS rotational constants and the inertial defects were improved by at least two orders of magnitude (see Table ). With such a degree of accuracy, we can conclude that the inertial defect is not dependent on the conformation as it was neither isomeric dependent by considering the results obtained on 2‐MP and 4‐MP in UV . Nevertheless, our experimental results show an increasing of the inertial defect with the excitation of the methoxy out‐of‐plane bending as it was already observed in the MW domain by Caminati et al .…”
Section: Figuresupporting
confidence: 79%
“…Compared to the UV measurements, the accuracies of the GS rotational constants and the inertial defects were improved by at least two orders of magnitude (see Table ). With such a degree of accuracy, we can conclude that the inertial defect is not dependent on the conformation as it was neither isomeric dependent by considering the results obtained on 2‐MP and 4‐MP in UV . Nevertheless, our experimental results show an increasing of the inertial defect with the excitation of the methoxy out‐of‐plane bending as it was already observed in the MW domain by Caminati et al .…”
Section: Figuresupporting
confidence: 79%
“…The 3MP isomer exhibits the richest conformational landscape with four stable conformers at room temperature, namely 3MP-C1 to 3MP-C4 (see Fig. 3a), as evidenced by previous rotationally resolved spectroscopic studies [8,11]. In the far-IR, the ν 6 out-of-plane OH bending mode has a very strong band intensity (I harm > 90 km/mol) compared to the other low-frequency vibrations (I harm < 10 km/mol) which are most probably below our detection limit.…”
Section: A3 Vibrational and Conformational Analysissupporting
confidence: 68%
“…These studies emphasized the congestion of lines in MPs spectra due to rather small rotational constants and the presence of several conformers and pure rotational transitions within the low-lying vibrational excited states. To the best of our knowledge, the only high resolution rovibrational data on MPs have been obtained at low temperature by the group of T. Zwier [10] and the group of M. Schmitt [11,12] using respectively free-jet fluorescence dip infrared spectroscopy and molecular beam rotationally resolved electronic spectroscopy. While the first group focused on the anharmonic coupling in the C-H stretch region, the second group provides MP conformational analyses in the electronically excited states.…”
Section: Introductionmentioning
confidence: 99%
“…30 Recently, gas-phase intramolecular structural dynamics investigations involving methoxyphenol isomers showed that the rotational barrier of the OH substituent in 2methoxyphenol is significantly higher than that of 3-and 4methoxyphenol in their ground states. 38 The high rotational barrier for the 2-methoxyphenol was found to be the result of an intramolecular hydrogen-bond established between the OH group and the methoxy group, resulting in a rotation of the methoxy group out of the plane of the ring by up to 13.5°. 38 Recently, we have studied the adsorption of phenol on RANEY® Ni in presence of cyclohexane as the solvent at 40°C.…”
Section: Atr-ir Spectroscopymentioning
confidence: 98%
“…38 The high rotational barrier for the 2-methoxyphenol was found to be the result of an intramolecular hydrogen-bond established between the OH group and the methoxy group, resulting in a rotation of the methoxy group out of the plane of the ring by up to 13.5°. 38 Recently, we have studied the adsorption of phenol on RANEY® Ni in presence of cyclohexane as the solvent at 40°C. 39 This study successfully revealed key features of co-adsorption of phenols, alcohols and polyols on the complex surface of this catalyst.…”
Section: Atr-ir Spectroscopymentioning
confidence: 98%